Degradasi komponen serat serbuk gergaji hasil biokonversi jamur tiram putih (Pleurotus ostreatus) dengan level urea berbeda - Rip Krishaditersanto (Faculty of Animal Science, Universitas Brawijaya, 2018)
This study aims to determine the effect of urea supplementation on substrate to the change percentage content of crude fibre component of sawdust as the yield of bioconversion by Pleurotus ostreatus with 40 days incubation period. The design used was Complete Random Design (CRD) with 4 levels of urea that is P0 = sawdust substrate + 0% urea; P1 = sawdust substrate + 0.5% urea; P2 = sawdust substrate + 1% urea; P3 = sawdust substrate + 1.5% urea;and P4 = sawdust substrate + 2% urea, with 3 replicates at each treatment. The parameters observed were the change percentage content of Neutral Detergent Fibre (NDF), Acid Detergent Fibre (ADF), hemicellulose, cellulose, and lignin. From the observation on the growth of myceliumseen on P2 is the best. The percentage decrease in the content of all fiber components in P2 is the highest. Analyzed data using analysis of variance, showed that urea supplementation had significant effect (P <0,05) to the change percentage content of Neutral Detergent Fibre (NDF), Acid Detergent Fibre (ADF), hemicellulose, cellulose, and lignin. Bioconversion of sawdust by Pleurotus ostreatus with level of urea supplementation 1% yields the highest of the change percentage content of crude fibre component.